Традиції художнього дерева і металу Гуцульщини - Юсипчук, Ю. (Інститут народознавства НАН України, 2007)
The article defines some main stages in development of latest creative traditions of artistic wood and metal. A five-step model of evaluation is being used in the study. A weakening of artistic tradition presented as a result of complicated social and economical circumstances.